Computed tomography-guided microwave ablation of perivascular liver metastases from colorectal cancer: a study of the ablation zone, feasibility, and safety. (1st January 2021) - Izaaryene, Jean; Drai, Maxime; Deniel, Cécile; Bridge, Pauline; Rico, Geoffrey; Daidj, Nassima; Gilabert, Marine; Ewald, Jacques; Turrini, Olivier; Piana, Gilles
Abstract: Objectives: To compare the ablation margins and safety of microwave ablation (MWA) of perivascular versus non-perivascular liver metastases from colorectal cancer (CRC) and to determine the risk factors for local tumor progression (LTP) after perivascular MWA. Methods: Between June 2017 and June 2019, 84 metastases were treated: 39 perivascular (<5 mm from a vessel >3 mm), and 46 non-perivascular. Perivascular metastases were treated with either conventional or optimized protocols (maximum power and/or several heating cycles after repositioning the needle regardless of the initial tumor dimensions). The mean diameter of metastases was 15.4 mm (SD: 7.56). Results: Vascular proximity did not result in a significant difference in ablation margins. The technical success rate, primary efficacy, and secondary efficacy were 90%, 66%, and 83%, respectively. Perivascular location was not a risk factor for time to LTP ( p = 0.49), RFS ( p = 0.52), or OS ( p = 0.54). LTP was statistically related to the presence of a colonic obstruction ( p < 0.05), number of metastases at the time of diagnosis ( p < 0.05), type of protocol ( p < 0.05), ablation margins ( p < 0.001) and LTP was proportional to the number of liver resections before MWA ( p < 0.05). There was no LTP in tumors ablated with margins over 10 mm. Two grade 4 complications occurred. Conclusion: MWA is an effective and safe treatment for perivascular liver metastases from CRC, provided that satisfactory margins are achieved. A maximalist attitude could be related to better local control.